Zinc coatings of high hardness on steel by electrodeposition from glutamate complex baths. (July 2014) - Ibrahim, M. A. M.; Bakdash, R. S.
<x content-type="archive" xml:space="preserve">Abstract</x> The effect of monosodium glutamate (MSG) on zinc electrodeposition from acidic sulphate plating baths was investigated using potentiodynamic cathodic polarisation, cyclic voltammetry, cathodic current efficiency and throwing power measurements, current–time transients and in-situ anodic linear stripping voltammetry techniques, complemented with X-ray diffraction analysis and SEM measurements. Addition of MSG increases the hardness of zinc deposits by a factor of 3. Kinetic parameters such as Tafel slope, transfer coefficient and exchange current density obtained from Tafel plots, indicated that MSG had a pronounced accelerating effect on the zinc deposition process. From the voltammetric data obtained in the presence of MSG, it is clear that the overpotential of zinc deposition is significantly decreased. Chronoamperometry measurement suggested that the growth of zinc metal is a diffusion-controlled process. X-ray diffraction analysis and SEM observations revealed that MSG does not change the crystal structure of the electrodeposited zinc but strongly affected the crystallographic orientation of the crystal planes.